2017
DOI: 10.3390/ma10080923
|View full text |Cite
|
Sign up to set email alerts
|

Multiaxial Fatigue Damage Parameter and Life Prediction without Any Additional Material Constants

Abstract: Based on the critical plane approach, a simple and efficient multiaxial fatigue damage parameter with no additional material constants is proposed for life prediction under uniaxial/multiaxial proportional and/or non-proportional loadings for titanium alloy TC4 and nickel-based superalloy GH4169. Moreover, two modified Ince-Glinka fatigue damage parameters are put forward and evaluated under different load paths. Results show that the generalized strain amplitude model provides less accurate life predictions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 52 publications
1
61
0
Order By: Relevance
“…To consider all the stress and strain components contributed to the fatigue damage on the critical plane, the generalized strain amplitude (GSA) model and the modified GSA (MGSA) model have been proposed by Ince‐Glinka and Yu, respectively, which are expressed as follows. GSA=τmaxτfΔγe2+Δγp2+σn,maxσfΔεne2+Δεnp2max=f1()Nf, where τ max and σ n ,max are the maximum shear stress and normal stress, respectively; Δ γ e /2 and normalΔεne/2 are the elastic shear strain amplitude and the elastic normal strain amplitude, respectively; Δ γ p /2 and normalΔεnp/2 are the plastic shear strain amplitude and the plastic normal strain amplitude, respectively; σf and τf are the fatigue strength coefficient and the shear fatigue strength coefficient, respectively; and f 1 ( N f ) is the function with respect to the number of cycles to failure N f .…”
Section: The Proposed Online Multiaxial Fatigue Damage Evaluation Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…To consider all the stress and strain components contributed to the fatigue damage on the critical plane, the generalized strain amplitude (GSA) model and the modified GSA (MGSA) model have been proposed by Ince‐Glinka and Yu, respectively, which are expressed as follows. GSA=τmaxτfΔγe2+Δγp2+σn,maxσfΔεne2+Δεnp2max=f1()Nf, where τ max and σ n ,max are the maximum shear stress and normal stress, respectively; Δ γ e /2 and normalΔεne/2 are the elastic shear strain amplitude and the elastic normal strain amplitude, respectively; Δ γ p /2 and normalΔεnp/2 are the plastic shear strain amplitude and the plastic normal strain amplitude, respectively; σf and τf are the fatigue strength coefficient and the shear fatigue strength coefficient, respectively; and f 1 ( N f ) is the function with respect to the number of cycles to failure N f .…”
Section: The Proposed Online Multiaxial Fatigue Damage Evaluation Methodsmentioning
confidence: 93%
“…Analyzing the predicted results of the MGSA damage parameter in Yu et al and the GSA damage parameter in Ince and Glinka, a definite conclusion can be obtained that the MGSA model provides relatively nonconservative predictions compared with the GSA model. That is, in the MGSA model, the normalization of the plastic strain terms in Equation can make the predictions nonconservative.…”
Section: The Proposed Online Multiaxial Fatigue Damage Evaluation Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Suspension history condition monitoring data usually contain useful information revealing the degradation situation of the system, including environmental factors and loading variations in actual situations, such as degradations and variations of stress amplitudes [10][11][12]34,35]. If these data are properly used, it is helpful to estimate RUL more accurately, particularly when the failure data are insufficient and unavailable in some cases [36,37]. Li et al [38] used the suspension data to promote the prediction precision of a neural network.…”
Section: Introductionmentioning
confidence: 99%
“…New multiaxial approaches are being developed based on the critical plane method using local strain energy. 12,13 The probabilistic method of Zhu et al 14 is capable of considering the usual scatter found in material parameters in the multiaxial low-cycle fatigue (LCF) assessment. Special attention has been given lately to the fatigue assessment of components operating under high temperatures.…”
Section: Introductionmentioning
confidence: 99%